Effects of wearing a customized bite-aligning mouthguard on powerful actions in highly trained swimmers - Miró, A.; Buscà, B.; Solana-Tramunt, M.; Aguilera-Castells, J.; Arboix-Alió, J.; Vergnoux, F.; Arellano, R. (Journal of Exercise Science & Fitness, 2021)
The potential advantages of wearing customized bite-aligning mouthguards on several performance parameters such as muscular strength, power and reaction time have been reported. Literature shows that the concurrent activation potentiation phenomenon, elicited by a powered and balanced jaw clenching, can provide athletes with several neuromuscular advantages. The aim of the present study was to investigate the acute effects of jaw clenching while wearing a customized bite-aligning mouthguard on swimming start, countermovement jump and swim bench test, in contrast to two other conditions: non-jaw clenching and jaw clenching without mouthguard. Methods: A randomized, repeated measure within study design was used to compare the condition effect on eight highly trained elite male and female swimmers. Results: Statistical analysis revealed a significant increase in the countermovement jump height (p=0.041) when comparing the use of mouthguards with the non-jaw condition. In the swim bench, a significant greater time to peak force (p=0.049) was found when comparing the use of mouthguards with the jaw condition. Although, non-significant effects, small differences were found in the start reaction time and 15-m freestyle swimming when comparing the use of mouthguards with the non-jaw condition. Conclusion: This study demonstrated that wearing customized, bite-aligning mouthguards had an ergogenic effect on specific measures of vertical jump and swim bench test, whereas non-meaningful but small differences were found in swimming start